2003
DOI: 10.1021/jm0302391
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of 6-Substituted-3-(4-methanesulfonylphenyl)-4-phenylpyran-2-ones:  A Novel Class of Diarylheterocyclic Selective Cyclooxygenase-2 Inhibitors

Abstract: A group of 6-alkyl (alkoxy or alkylthio)-4-aryl-3-(4-methanesulfonylphenyl)pyran-2-ones (14a-v), possessing either a H or F substituent at the para-position of the C-4 phenyl ring, were designed for evaluation as selective cyclooxygenase-2 (COX-2) inhibitors with in vivo antiinflammatory-analgesic activities. Although 6-ethylthio-3-(4-methanesulfonylphenyl)-4-phenylpyran-2-one (14s) exhibited a very high in vitro COX-2 inhibitory potency (IC(50) = 0.0032 muM) and COX-2 selectivity (SI > 120 000), 14s exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Several derivatives of 6-alkyl (alkoxy or alkylthio)-4-aryl-3-(4-methanesulfonylphenyl)pyrones 49 had been synthesized to get insights into structure activity relationships, whereby 6-methyl-3-(4-methanesulfonylphenyl)-4-phenylpyran-2-one ( 50 ) showed the best combination of inhibitory concentration and selectivity (IC 50 = 0.68 µM, SI = 904; Fig. 11 ) [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Several derivatives of 6-alkyl (alkoxy or alkylthio)-4-aryl-3-(4-methanesulfonylphenyl)pyrones 49 had been synthesized to get insights into structure activity relationships, whereby 6-methyl-3-(4-methanesulfonylphenyl)-4-phenylpyran-2-one ( 50 ) showed the best combination of inhibitory concentration and selectivity (IC 50 = 0.68 µM, SI = 904; Fig. 11 ) [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Chemical compounds containing an α-pyrone moiety are widespread in nature [ 1 2 ] and show a high diversity in their biological activity. Members of this class of compounds have been identified with antimicrobial, cytotoxic [ 3 ] and antitumor activities [ 4 ], as HIV protease inhibitors [ 5 ] and selective COX-2 inhibitors [ 6 ]. Recently, it was shown that photopyrones ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Both COX-1 and COX-2 inhibitory activities were evaluated using a COX colorimetric inhibitor screening assay kit (Catalog No. 701050, Cayman Chemical Inc., Ann Arbor, MI, USA) according to the previous reports [26][27][28]. The pyrrolizines 12-18 were tested against indomethacin (as a nonselective COX inhibitor) and celecoxib (as a selective COX-2 inhibitor).…”
Section: In Vitro Cox Inhibitory Assaymentioning
confidence: 99%
“…701050). The assay was carried out according to the manufacturer's instructions and as described before [26][27][28].…”
Section: Chemistrymentioning
confidence: 99%